The atlas of endangered places - Pollock, Steve (Stephen Thomas) (New York Facts on File, 1993)
Text and maps focus on areas of the world in which human activity is destroying the natural balance.
"First published in the UK in 1993 by Belitha Press Limited"--T.p. verso.
Keywords: Man -- Influence on nature -- Maps for children; Children's atlases; Man -- Influence on nature -- Maps; Man -- Influence on nature; Pollution -- Maps for children; Pollution -- Maps; Pollution